The 5S ribosomal RNAs of Paracoccus denitrificans and Prochloron. - MacKay, R M (1982)
The nucleotide sequences of the 5S rRNAs of Paracoccus denitrificans and Prochloron sp. are (formula: see text), respectively. Specific phylogenetic relationships of P. denitrificans with purple non-sulphur bacteria, and of Prochloron with cyanobacteria are demonstrated, and unique features of potential secondary structure are described.